Hadith Criticism Mapping in Indonesia: Bibliometrics Analysis 2016-2022 - ananda, yassinta; Wendry, Novizal; Arwendria, Arwendria (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this research is to conduct bibliometrics analysis toward hadith mapping criticism in Indonesia ranging from 2016 to 2022 through data gathered from Google Scholar. The highlighted aspects are the main author, collaboration network, and the growing trend of hadith criticism. The data obtained is read by using quantitative method through Rbiblioshiny package. The finding of this research shows Wahyudin Darmalaksana as the most productive author with significant contribution toward hadith criticism. As for the limited collaboration in groups and the most quoted writing is written by Latifah Anwar. The trend shows a significant focus toward the view of Al-Ghazali about hadith criticism and the implementation of Schacht theory.